Arbitration in space disputes. (29th October 2019) - Frohloff, Jan
Abstract: Some 40 years ago, the advent of commercial space activities was expected to usher in an era of disputes between the various actors in outer space. However, these space disputes and potential arbitrations between private or public entities never seemed to materialize. Even until recently it was suggested that disputes in outer space are an emerging issue which needs to be addressed in the future. The author takes the opposite position, arguing that arbitration in space disputes is an active field in commercial and investment arbitration, and discussing the most notable cases and their particularities.